2018
DOI: 10.1021/acs.jpca.8b07953
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Electronic Polarization Corrections to the Dielectric Constant of Water

Abstract: The standard approach to calculating the dielectric constant from molecular dynamics (MD) simulations employs a variant of the Kirkwood–Fröhlich methodology. Many popular nonpolarizable models of water, such as TIPnP, give a reasonable agreement with the experimental value of 78. However, it has been argued in the literature that the dipole moments of these models are effective, being smaller than the real dipole of a liquid water molecule by about a factor of , or roughly . If the total or corrected dipole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…However, a recent paper by Farahvash et al 15 shed some new light on this issue by comparing the performance of several popular non-polarizable water models. They observed that application of the MDEC approach (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent paper by Farahvash et al 15 shed some new light on this issue by comparing the performance of several popular non-polarizable water models. They observed that application of the MDEC approach (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Another issue that warrants further exploration is the effect of scaling on the dynamic dielectric response of fluids 15,48 . Indeed, it has been recently shown that, at least for some fluids, classical non-polarizable models are able to describe the dynamic response over a wide range of frequencies, provided the simulation results are scaled to match the corresponding experimental static dielectric constant 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on electrostatic models have raised questions regarding whether the simulated dielectric constant requires post hoc corrections. , These studies posit that the effective electrostatic moments used to compute the MM interactions of ions and polar species should be reduced with respect to the physical charges used to compute electrostatic properties due to the dielectric screening caused by the electronic polarization of the medium. This implies that the dielectric constant computed from the partial charges in the force field should be increased by a correction prior to comparing with the experiment, or conversely, the experimental value should be reduced prior to making the comparison with the force field.…”
Section: Resultsmentioning
confidence: 99%
“…In ref , the authors concluded that the missing polarizability in nonpolarizable models scales the dielectric constant by a factor of 1.78. Under the assumption that the same correction factor would apply to our models, the reference dielectric constant should be reduced by a factor of 1/1.78 = 0.5618.…”
Section: Resultsmentioning
confidence: 99%
“…Polarization has been found to lead to artifacts during MD simulations of proteins, 9,10 and methods to address this problem have been proposed. 44,45 However, it remains to be addressed for the more polar nucleic acids. From our quantum mechanics (QM) calculations, it was observed that a water molecule bridged by two polar atoms experienced an overall potential unequal to the sum of the two individual potentials (Figure 8).…”
Section: E E Ementioning
confidence: 99%